The Existence of Siri Culture In The Era of Digital Community, Sulawesi Selatan - Nursalam Nursalam; St Haniah; Wahyuddin Hamid (Publikasi Indonesia, 2023)
The existence of siri' culture has been demonstrated by the implementation of local wisdom which is still maintained today. Unity, mutual assistance, and village community concern for one another show a form of siri' culture that is still quite strong within the village community. The siri' culture is culturally shown through 5 types of local wisdom that still exist, namely: Marakka bola, Masarappo or mabbaruga or mawalasuji, community service, and mutual cooperation. The perspective of the Village Community regarding siri' culture received various responses. Siri' culture according to the social view is shown from the manners shown by someone. How to behave and treat others. In addition, someone who always takes care of his siri' will also be maintained and will get treatment and appreciation from other people because he is good at taking care of himself.